Structural conditions of typical urban areas and electoral support for an Islamist party: The case of the Prosperous Justice Party in Depok Jaya and Cinangka, Depok City, Indonesia - Alamsyah, Andi Rahman (Kasetsart Journal of Social Sciences, 2026)
The Partai Keadilan Sejahtera (PKS) or Prosperous Justice Party is an Islamist party that gained significant electoral support in Indonesia after the fall of the New Order regime. According to several studies, this is a reflection of the phenomenon of urban Muslim middle class as its socio-political base. However, in several areas with similar characteristics, electoral support for PKS has been less than impressive. The author argues that differences in structural conditions typical of urban areas, including Islamic character, type of settlement, migration status, presence of ethnic groups and Islamic organizations, also play a role in determining this support. This Islamist party tends to gain significant support in urban areas with less assertive Islamic character, with most of the population living in housing complexes and being migrants, and ethnic grouping and Islamic organizations not having influence in society. These conditions make it easier for the Islamist party to gain electoral support. In urban areas where the opposed condition occurs, the Islamist party tends to gain less significant support.